Abordagens etnográficas sobre pessoas em situação de refúgio e inserção laboral - Carla Cristina de Paula Gomes (2023)
Having as subject of observation the people in refuge situation and work as a phenomenon of interest, this thesis aims to understand the labor insertion of these subjects and their experiences from some cases collected through an ethnographic approach. The comparison of the expanded definition of refugees in Act nº 9.474, of July 22, 1997 - which implemented the 1951 Refugee Statute -, and the other concepts contained in the New Migration Law - NLM (Act nº 13.445, of May 24, 2017) and in its regulatory decree (Decree nº 9.199, of November 20, 2017), with the records and reports of this group of individuals revealed the following reality: the difficulties faced by refugees, asylum seekers and shelters, all migrants, in their labor insertion. Their experiences show impediments that harm their habitation in the host country and in the city where they choose to live or even stay, even if only temporarily. The analysis of the records collected (documents; acts; judicial and administrative decisions) and reports obtained through interviews with these people in a refugee situation brings to light the exclusion they experienced in multiple situations: legal and administrative restrictions; judicial decisions that are obstructive to the exercise of work; difficulties in renewing the residence permit, unavailability of economic resources for their full reception. Parts of experiences lived and focused on observation allow the portrayal of a whole: foreigners restricted in their dignity and without work, despite the provision of these grounds in the Federal Constitution of 1988. The search for alternatives to face or alleviate these situations permeates the rereading of Human Rights, in its multicultural conception, without abstaining, however, from the narratives of its local incidence, enabling these people to leave their condition of refuge and become migrant workers, welcomed beyond the walls.